What is the difference between pluralism and inclusivism? - Harun Abdullah; Djafar Djafar; Nurhadi Nurhadi (Bata Ilyas Educational Management Review, 2024)
Social life provides many lessons to every society or people in their life on earth and in the course of life humans are equipped with the ability to think to be able to understand the natural surroundings, but the ability to think is not enough without guidance that leads humans to live in an orderly manner and this is only can be obtained in an understanding of religiosity as a guide in living life. Humans certainly understand very well that thoughts that are not guided by religiosity or religion can become uncontrolled, which can result in damage to the natural environment and the social environment. To understand this, the author conducted research in the form of qualitative descriptive research to see how social life has a religious nuance by trying to understand religious inclusivism and pluralism which also touches on exclusivism. The results of the research show that the religious view of exclusivism states that the most correct is the group or the most correct religion is the religion or belief that one adheres to. However, Christians have a slightly different view of exclusivism and state that truth and salvation only exist in Christianity and religions other than them do not bring salvation therefore those of other religions must be Christianized. Furthermore, the inclusivism view was born to perfect the exclusivism view where the general understanding of inclusivism states that inclusivism is an understanding that considers truth to be shared by all groups. or understanding which assumes that truth is not only found in one group, this is based on a belief that every religion carries the teachings of salvation. The substance of all religions is the same, but they have different requirements and teachings. Likewise, religious pluralism is a concept that has a broad meaning, relating to the acceptance of different religions which are practiced in their own ways and respect each other.